Effect of Murottal Surah Ar-Rahman Therapy on Stress Reduction among Primigravida Women in the Third Trimester - Sutrisari Sabrina Nainggolan; Silatur Rahmi Eldaini; Abu Bakar Sidik (Minsight: Midwifery Insight and Innovation Journal, 2025)
Stress is one of the most common psychological problems experienced by pregnant women, particularly among primigravid mothers who are expecting their first child. This condition often arises due to anxiety, fear, and negative thoughts regarding pregnancy and childbirth. Internal and external factors, such as emotional changes, family support, and social environment, can influence the mother’s psychological wellbeing. The third trimester is considered the most critical phase, as physical discomfort and emotional instability tend to increase during this period. This study aimed to determine the effect of Murottal Surah Ar-Rahman therapy on stress levels among primigravid pregnant women in their third trimester. The research employed a quantitative pre-experimental design with a one-group pre-test–post-test approach. The sample consisted of 18 primigravid pregnant women selected through purposive sampling. Data were collected using a modified Depression Anxiety Stress Scale (DASS) questionnaire administered before and after therapy. The results showed that before receiving therapy, 5 respondents (27.78%) experienced mild stress and 13 respondents (72.22%) experienced moderate stress. After therapy, 11 respondents (61.11%) had normal stress levels and 7 respondents (38.89%) experienced mild stress. Statistical analysis revealed a significant difference (p = 0.000) between pre-test and post-test scores, indicating that Murottal Surah Ar-Rahman therapy effectively reduced stress levels among primigravid pregnant women. The study concludes that listening to Murottal Surah Ar-Rahman can serve as a simple, non-pharmacological intervention to support emotional stability and promote mental health in pregnant women during the third trimester.